Continuous flow telescopic oxidation of alcohols via generation of chlorine and hypochlorite - Sharma, Y.; Moolya, S.; Joshi, Ramesh A.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2017)
A 3-step continuous flow oxidation of alcohols is demonstrated with continuous generation of chlorine as the first step followed by its use for the flow synthesis of high strength sodium hypochlorite. The solution is subsequently used for oxidation of alcohols in the presence of a catalytic amount of the nitroxyl radical “TEMPO”, which inhibits oxidation at the aldehyde stage. Selective oxidations of eight different alcohols were demonstrated. To achieve identical yields, the aromatic alcohols containing electron withdrawing groups needed a longer residence time than aliphatic alcohols.